Colombian Language Teachers Abroad: An Overview of Their Professional Experience - Liana Mercedes Torres-Casierra (Asociación Colombiana de Profesores de Ingles, 2021)
This article presents the preliminary results of an enquiry on the work experience of Colombian language teachers who have entered the workforce in foreign countries. The study aims at unveiling aspects of the personal and professional experience of those graduates that might be relevant for pre-service teachers in local degree programs ahead of their potential move abroad in a growing international mobility context. The study includes data from surveys and personal interviews carried out with a group of 26 participants whose narratives of experience invite one to consider the variables that may either facilitate or hinder one's teaching practice in a foreign workplace and the intercultural communication issues that language teachers may need to deal with. A reflection is brought forward on the needs that teacher training programs at university level in Colombia should address to broaden the scope of their graduates' likely move abroad.